2020
DOI: 10.21203/rs.3.rs-56252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Value of laboratory tests in COVID-19 hospitalized patients for clinical decision-makers: a predictive model, using data mining approach

Abstract: Purpose: Because of the rapid increase in confirmed cases of COVID-19, in particular those with severe or critical status, overwhelming of health systems is a worldwide concern. Therefore, identifying high-risk COVID-19 patients, can help service providers for priority setting and hospital resource allocation. Methods: 4542 adult patients with confirmed COVID-19 admitted in 15 hospitals in Tehran, Iran, from Feb 20 to April 18, 2020 were included in this retrospective cohort study with final outcomes of surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…In contrast to the present study, which pre-dicted mortality of COVID-19 patients based on symptoms, signs, laboratory tests, and demographic characteristics, Mousavi et al [14] identified high-risk COVID-19 patients based on only laboratory tests. In this study, the sample size (n=4542) was higher than the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…In contrast to the present study, which pre-dicted mortality of COVID-19 patients based on symptoms, signs, laboratory tests, and demographic characteristics, Mousavi et al [14] identified high-risk COVID-19 patients based on only laboratory tests. In this study, the sample size (n=4542) was higher than the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…However, unlike the present study, in which all people with COVID-19 disease were included at any age, in this study, only the COVID-19 patients aged over 18 years were studied. Also, in contrast to the present study, which used four different data mining models, in the study conducted by Mousavi et al [14], logistic regression was used to compare recovered and dead patients in the SPSS environment. The highest accuracy in the present study was reported at 99.14% using the KNN2 algorithm.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations